Fine grinding and anti-oxidation treatment process for surface of reflective film
By adding benzotriazole to the reflective film abrasive liquid and using spraying process to perform anti-oxidation treatment, the problem of the existing reflective film's oxidation resistance is solved, and a more uniform and dense anti-oxidation coating is achieved, and the overall quality of the reflective film is improved.
Patent Information
- Application Number
- CN202411644610.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing anti-oxidation treatment method of brush or roller coating after the polishing of the reflective film is used, which makes it difficult for the anti-oxidation coating to fill the microscopic pores and is easily penetrated by oxygen, resulting in the problem of insufficient anti-oxidation properties.
The process of adding benzotriazole to the abrasive liquid is adopted to perform anti-oxidation treatment through the spraying process to ensure that the anti-oxidation coating is uniformly and thoroughly coated, and dried through a dryer.
It effectively improves the anti-oxidation properties of the reflective film, ensures the uniformity and density of the anti-oxidation coating, thereby improving the overall quality and service life of the reflective film.
Smart Images

Figure CN119501803A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of reflective films, in particular to a process for fine grinding and anti-oxidation treatment of the surface of a reflective film. Background Art
[0002] Reflective film is a functional material widely used in many fields such as transportation and safety. It is composed of a variety of special materials, and the surface usually has tiny glass beads or micro-prism structures. Its core principle is to be able to reflect the light irradiated on the surface of the film back at a specific angle, thereby greatly improving the visibility of the marked object in a dark environment. In the field of transportation, reflective film is widely used in road signs, vehicle license plates, and body reflective signs. For example, at night or in low-visibility weather, the reflective film on the road sign allows the driver to clearly identify traffic information at a long distance, effectively guide traffic flow, and reduce the risk of accidents. The reflective signs on the vehicle enhance the recognizability of the vehicle itself, so that other road users can detect the position and outline of the vehicle in time. In terms of safety protection, reflective film is also used in work clothes, warning tapes, etc. to ensure the safety of workers in complex environments. With its unique reflective properties, reflective film plays an indispensable and important role in ensuring traffic safety and improving the level of safety protection. With the development of technology, its reflective efficiency, durability and other properties are constantly being optimized and improved.
[0003] Existing reflective films are only treated with anti-oxidation by brushing or roller coating after being polished. Anti-oxidation coatings are difficult to fill in some microscopic pores or defects, which make them more easily penetrated by oxygen, resulting in the problem of short-lasting anti-oxidation properties. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a process for fine grinding and anti-oxidation treatment of the surface of a reflective film, which solves the problem that the existing reflective film is only subjected to anti-oxidation treatment by brushing or roller coating after grinding, and the anti-oxidation coating is difficult to fill in some microscopic pores or defects, which makes it easier for oxygen to penetrate, resulting in the problem of short-lasting anti-oxidation property.
[0005] To achieve the above purpose, the present invention is implemented by the following technical scheme: The process of fine grinding and anti-oxidation treatment of the surface of the reflective film includes the following steps:
[0006] S1. Preparation before grinding: prepare 120-1200 mesh silicon carbide grinding sand, prepare grinding liquid containing benzotriazole, use a dust-free cloth dipped in ethanol to clean the surface of the reflective film, and then fix the reflective film on the surface of the grinder workbench;
[0007] S2, coarse grinding stage: spread 120-180 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 1000-1500 rpm and the pressure to 3-5kg / cm 2 , start supplying the benzotriazole-containing grinding liquid;
[0008] S3, intermediate grinding stage: spread 220-320 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 800-1200 rpm and the pressure to 2-4kg / cm 2 , continuously supplying benzotriazole-containing grinding liquid;
[0009] S4, fine grinding stage: Spread 320-1200 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 500-800 rpm and the pressure to 1-3kg / cm 2 , continuously supplying benzotriazole-containing grinding liquid;
[0010] S5. Anti-oxidation treatment: clean the residual impurities after grinding, then spray the anti-oxidation coating with a spray gun, and dry it with a dryer after spraying.
[0011] Preferably, the grinding liquid containing benzotriazole in S1 comprises the following raw materials in parts by weight: 70-90 parts of deionized water, 5-15 parts of silicon carbide, 0.5-1 parts of benzotriazole, 1-3 parts of polyethylene glycol, 1-3 parts of oleic acid, and 0.5-1.5 parts of sodium dodecyl sulfate, and the silicon carbide has a mesh size of 120-1200.
[0012] The components of the grinding liquid raw material containing benzotriazole are weighed according to the formula, and the grinding liquid raw material containing benzotriazole is put into a stirrer, and the speed of the stirrer is controlled at 15-60 rpm, and the stirring time is controlled at 20-30 minutes.
[0013] The grinding time in S2 is 10-20 minutes, the surface roughness is monitored by a roughness measuring instrument, and the surface roughness Ra is controlled to be 1-2 μm. The grinding time in S3 is 15-30 minutes, and the surface roughness Ra is controlled to be 0.45-0.85 μm. The grinding time in S4 is 30-60 minutes, and the surface roughness Ra is controlled to be 0.1-0.3 μm.
[0014] Preferably, the anti-oxidation coating in S5 comprises the following raw materials in parts by weight: 40-70 parts of a film-forming substance, 20-40 parts of a solvent, 1-5 parts of titanium dioxide, 1-5 parts of mica powder and 1-10 parts of an additive.
[0015] Preferably, the film-forming substance includes the following raw materials in percentage: 30%-50% of silicone resin and 25%-50% of acrylic copolymer, the solvent includes the following raw materials in percentage: 15%-30% of xylene, 15%-40% of butyl acetate, and 20%-30% of deionized water, and the auxiliary agent includes the following raw materials in percentage: 30%-80% of isocyanate curing agent, 5%-20% of silicone leveling agent, and 1%-10% of defoaming agent.
[0016] Preferably, the components of the anti-oxidation coating raw materials are weighed according to the formula, and the anti-oxidation coating raw materials are put into a mixer, the speed of the mixer is controlled at 25-75 rpm, and the stirring time is controlled at 10-15 minutes.
[0017] Preferably, the spraying pressure in S5 is 0.3-0.5MPa, the distance between the spray gun and the surface of the reflective film is maintained at 20-30cm, the spraying is divided into three times, and the interval between each time is 5-10 minutes. The final spraying thickness is controlled at 5-10μm, the drying temperature of the dryer is controlled at 80-100℃, and the drying time is controlled at 2-3 hours.
[0018] The present invention provides a process for fine grinding and anti-oxidation treatment of the surface of a reflective film.
[0019] Beneficial effects:
[0020] 1. In the present invention, 0.5-1 part of benzotriazole is added to the grinding liquid, so that the benzotriazole can be filled into the microscopic pores of the reflective film during grinding, so as to achieve the whole process of anti-oxidation, thereby improving the existing reflective film which is only anti-oxidation treated by brushing or roller coating after grinding. The anti-oxidation coating is difficult to fill in some microscopic pores or defects, which will be more easily penetrated by oxygen, resulting in the problem of short-lasting anti-oxidation property.
[0021] 2. In the present invention, the final anti-oxidation treatment is carried out by using a spraying process, so that the anti-oxidation coating can be applied more evenly and thoroughly. By spraying three times with an interval of 5-10 minutes between each time, the uniformity of the final anti-oxidation coating can be further improved, making the anti-oxidation coating smooth and dense, thereby improving the anti-oxidation ability and overall quality of the reflective film. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a flow chart of the manufacturing process of the present invention;
[0023] Figure 2 Process flow chart for anti-oxidation treatment. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Please see attached Figure 1 The embodiment of the present invention provides a process for fine grinding and anti-oxidation treatment of the surface of a reflective film, which is characterized by comprising the following steps:
[0026] S1. Preparation before grinding: prepare 120-1200 mesh silicon carbide grinding sand, prepare grinding liquid containing benzotriazole, use a dust-free cloth dipped in ethanol to clean the surface of the reflective film, and then fix the reflective film on the surface of the grinder workbench;
[0027] S2, coarse grinding stage: spread 120-180 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 1000-1500 rpm and the pressure to 3-5kg / cm 2 , start supplying the benzotriazole-containing grinding liquid;
[0028] S3, intermediate grinding stage: spread 220-320 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 800-1200 rpm and the pressure to 2-4kg / cm 2 , continuously supplying benzotriazole-containing grinding liquid;
[0029] S4, fine grinding stage: Spread 320-1200 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 500-800 rpm and the pressure to 1-3kg / cm 2 , continuously supplying benzotriazole-containing grinding liquid;
[0030] S5. Anti-oxidation treatment: clean the residual impurities after grinding, then spray the anti-oxidation coating with a spray gun, and dry it with a dryer after spraying.
[0031] The grinding liquid containing benzotriazole in S1 includes the following raw materials in parts by weight: 70-90 parts of deionized water, 5-15 parts of silicon carbide, 0.5-1 parts of benzotriazole, 1-3 parts of polyethylene glycol, 1-3 parts of oleic acid, 0.5-1.5 parts of sodium dodecyl sulfate, and the silicon carbide has a mesh size of 120-1200.
[0032] Specifically, benzotriazole can penetrate into the reflective film during polishing to form a protective film, which prevents oxygen and moisture from contacting and thus prevents the reflective film from oxidizing. Deionized water can be mixed with other raw materials to prepare a grinding liquid, which helps benzotriazole and other ingredients to penetrate into the surrounding gaps of the reflective film during polishing to form a protective film in advance. Silicon carbide can play a polishing role so that the surface of the reflective film reaches the roughness required at different stages. Polyethylene glycol can play a role of dispersion and lubrication, which helps to improve the grinding effect and enable each ingredient to play a better role. At the same time, it may have a certain impact on the performance of the reflective film after surface treatment. Oleic acid can play a role of lubrication, dispersion and assistance to enable benzotriazole and other ingredients to better act on the surface of the reflective film, which helps to improve the grinding effect and anti-oxidation treatment effect. Sodium dodecyl sulfate can play a role of a surfactant, which helps to reduce the surface tension of the liquid, enable the grinding liquid to better infiltrate the surface of the reflective film, promote the role of each ingredient in the grinding process, and improve the grinding effect.
[0033] The grinding liquid raw material containing benzotriazole is weighed according to the formula, and the grinding liquid raw material containing benzotriazole is put into a mixer, and the speed of the mixer is controlled at 15-60 rpm, and the stirring time is controlled at 20-30 minutes.
[0034] Specifically, by placing the grinding liquid raw material containing benzotriazole into a mixer, controlling the mixer speed to 15-60 rpm, and controlling the stirring time to 20-30 minutes, the components can be fully mixed and evenly distributed, ensuring that effective ingredients such as benzotriazole are evenly distributed in the grinding liquid, thereby better playing its role in anti-oxidation and auxiliary grinding during the grinding process of the reflective film.
[0035] The grinding time in S2 is 10-20 minutes, the surface roughness is monitored by a roughness measuring instrument, and the surface roughness Ra is controlled at 1-2μm. The grinding time in S3 is 15-30 minutes, and the surface roughness Ra is controlled at 0.45-0.85μm. The grinding time in S4 is 30-60 minutes, and the surface roughness Ra is controlled at 0.1-0.3μm.
[0036] Specifically, the surface of the reflective film can be polished gradually and finely to meet the roughness standards required at different stages, thereby ensuring the flatness and smoothness of the reflective film surface and improving its reflective performance and overall quality.
[0037] The anti-oxidation coating in S5 comprises the following raw materials in parts by weight: 40-70 parts of film-forming substances, 20-40 parts of solvents, 1-5 parts of titanium dioxide, 1-5 parts of mica powder and 1-10 parts of additives.
[0038] Specifically, the film-forming substance can form a continuous and dense protective film on the surface of the reflective film, effectively blocking erosion factors such as oxygen and moisture, providing long-term anti-oxidation protection for the reflective film, and at the same time giving the coating good adhesion and physical properties to ensure the realization of the overall function of the coating. The solvent can dissolve the film-forming substance, titanium dioxide, mica powder, additives and other coating raw materials to evenly disperse the components, adjust the viscosity of the coating, and facilitate spraying construction. The film-forming substance evaporates during the drying process of the coating, so that the film-forming substance forms a uniform, continuous and dense protective film on the surface of the reflective film. Titanium dioxide can enhance the weather resistance of the coating and improve its resistance to oxidation. It can shield ultraviolet rays, increase the hardness and wear resistance of the coating, and may also play a certain auxiliary role in improving the anti-oxidation performance, thereby better protecting the reflective film. Mica powder can improve the shielding performance of the anti-oxidation coating, enhance the barrier effect on light and external factors, and improve the physical properties of the coating, such as increasing the flexibility of the coating and improving adhesion, thereby improving the protective effect and service life of the reflective film. Additives can improve the construction performance of the anti-oxidation coating, promote the curing reaction, and optimize the comprehensive performance of the coating after film formation, so that the anti-oxidation coating can better play a protective role on the surface of the reflective film and improve the quality and durability of the reflective film.
[0039] The film-forming substance includes the following raw materials in percentage: 30%-50% of silicone resin and 25%-50% of acrylic copolymer, the solvent includes the following raw materials in percentage: 15%-30% of xylene, 15%-40% of butyl acetate, and 20%-30% of deionized water, and the auxiliary agent includes the following raw materials in percentage: 30%-80% of isocyanate curing agent, 5%-20% of silicone leveling agent, and 1%-10% of defoaming agent.
[0040] Specifically, the silicone resin can provide excellent heat resistance, weather resistance, water resistance and good flexibility, so that the formed protective film can effectively resist external environmental erosion and enhance the long-term protective effect of the anti-oxidation coating on the reflective film. The acrylic copolymer can provide good adhesion, hardness, glossiness and chemical resistance. Xylene can dissolve coating components such as film-forming substances and adjust the viscosity of the coating. Butyl acetate can dissolve various components in the coating, adjust the volatilization rate and viscosity of the coating, and improve the leveling and construction performance of the coating. Deionized water can dissolve the coating raw materials, adjust the viscosity of the coating, participate in the film-forming process, ensure the stability of the coating, and help form a uniform and dense protective film. The oxidizing agent can react chemically with the active groups in the film-forming substance, promote the rapid curing of the coating, improve the hardness, wear resistance, chemical resistance and other properties of the paint film formed by the anti-oxidation coating on the surface of the reflective film, and enhance the durability and stability of the protective film. The silicone leveling agent can reduce the surface tension of the anti-oxidation coating, promote better leveling of the coating on the surface of the reflective film, reduce surface defects of the coating, make the formed protective film flatter and smoother, and improve the decorative and protective properties of the coating. The defoaming agent can eliminate the bubbles generated in the preparation and construction process of the anti-oxidation coating to prevent bubbles from remaining in the coating and affecting the density, flatness and protective properties of the coating, ensuring the formation of a uniform, continuous, bubble-free, high-quality protective film on the surface of the reflective film.
[0041] The components of the anti-oxidation coating raw materials are weighed according to the formula, and the anti-oxidation coating raw materials are put into a mixer, and the speed of the mixer is controlled at 25-75 rpm, and the mixing time is controlled at 10-15 minutes.
[0042] In S5, the spraying pressure is 0.3-0.5MPa, the distance between the spray gun and the surface of the reflective film is maintained at 20-30cm, and the spraying is divided into three times, with an interval of 5-10 minutes between each time. The final spraying thickness is controlled at 5-10μm, and the drying temperature of the dryer is controlled at 80-100℃, and the drying time is controlled at 2-3 hours.
[0043] Specifically, the anti-oxidation coating can be evenly and stably attached to the surface of the reflective film, forming a coating with appropriate thickness, flatness, density and good protective performance, while ensuring that the coating is fully cured, effectively improving the anti-oxidation ability and overall quality of the reflective film.
[0044] The following is further introduced in conjunction with specific embodiments:
[0045] Embodiment 1:
[0046] The process of fine grinding and anti-oxidation treatment of the reflective film surface includes the following steps:
[0047] S1. Preparation before grinding: prepare 120-1200 mesh silicon carbide grinding sand, prepare grinding liquid containing benzotriazole, use a dust-free cloth dipped in ethanol to clean the surface of the reflective film, and then fix the reflective film on the surface of the grinder workbench;
[0048] S2, coarse grinding stage: spread 120-180 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 1000-1500 rpm and the pressure to 3-5kg / cm 2 , start supplying the grinding liquid containing benzotriazole;
[0049] S3, intermediate grinding stage: spread 220-320 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 800-1200 rpm and the pressure to 2-4kg / cm 2 , continuously supplying benzotriazole-containing grinding liquid;
[0050] S4, fine grinding stage: Spread 320-1200 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 500-800 rpm and the pressure to 1-3kg / cm 2 , continuously supplying benzotriazole-containing grinding liquid;
[0051] S5. Anti-oxidation treatment: clean and grind residual impurities, then spray the anti-oxidation coating with a spray gun, and dry it with a dryer after spraying.
[0052] The grinding liquid containing benzotriazole in S1 includes the following raw materials in parts by weight: 80 parts of deionized water, 10 parts of silicon carbide, 0.5 parts of benzotriazole, 2 parts of polyethylene glycol, 2 parts of oleic acid, and 1 part of sodium dodecyl sulfate, wherein the silicon carbide has a mesh size of 120-1200.
[0053] Embodiment 2:
[0054] The difference between this embodiment and the above-mentioned embodiment 1 is that:
[0055] The grinding liquid containing benzotriazole in S1 includes the following raw materials in parts by weight: 80 parts of deionized water, 10 parts of silicon carbide, 0.75 parts of benzotriazole, 2 parts of polyethylene glycol, 2 parts of oleic acid, and 1 part of sodium dodecyl sulfate, wherein the silicon carbide has a mesh size of 120-1200.
[0056] Embodiment 3:
[0057] The difference between this embodiment and the above-mentioned embodiment 1 and embodiment 2 is that:
[0058] The grinding liquid containing benzotriazole in S1 includes the following raw materials in parts by weight: 80 parts of deionized water, 10 parts of silicon carbide, 1 part of benzotriazole, 2 parts of polyethylene glycol, 2 parts of oleic acid, and 1 part of sodium dodecyl sulfate, wherein the silicon carbide has a mesh size of 120-1200.
[0059] Table 1:
[0060]
[0061] The comparison in Table 1 is tensile strength, elongation at break, bending strength, hardness and glossiness. The standard values in Table 1 are obtained from experiments on reflective film made using a grinding liquid without adding benzotriazole. By changing the weight of benzotriazole in each embodiment, the results of Examples 1-3 in Table 1 are obtained. Table 1 shows that the durability of the reflective film can be effectively increased by adding benzotriazole to the grinding liquid.
[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. The reflective film surface is finely polished and anti-oxidation treated, which is characterized by: The following steps are involved: S1. Preparation before grinding: prepare 120-1200 mesh silicon carbide grinding sand, prepare grinding liquid containing benzotriazole, use a dust-free cloth dipped in ethanol to clean the surface of the reflective film, and then fix the reflective film on the surface of the grinder workbench; S2, coarse grinding stage: spread 120-180 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 1000-1500 rpm and the pressure to 3-5kg / cm 2 , start supplying the grinding liquid containing benzotriazole; S3, intermediate grinding stage: spread 220-320 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 800-1200 rpm and the pressure to 2-4kg / cm 2 , continuously supplying benzotriazole-containing grinding liquid; S4, fine grinding stage: Spread 320-1200 mesh silicon carbide grinding sand on the surface of the grinding pad, set the grinding machine speed to 500-800 rpm and the pressure to 1-3kg / cm 2 , continuously supplying benzotriazole-containing grinding liquid; S5. Anti-oxidation treatment: clean the residual impurities after grinding, then spray the anti-oxidation coating with a spray gun, and dry it with a dryer after spraying.
2. The process for fine grinding and anti-oxidation treatment of the reflective film surface according to claim 1, characterized in that: The grinding liquid containing benzotriazole in S1 includes the following raw materials in parts by weight: 70-90 parts of deionized water, 5-15 parts of silicon carbide, 0.5-1 parts of benzotriazole, 1-3 parts of polyethylene glycol, 1-3 parts of oleic acid, and 0.5-1.5 parts of sodium dodecyl sulfate. The silicon carbide has a mesh size of 120-1200.
3. The process for fine grinding and anti-oxidation treatment of the reflective film surface according to claim 2, characterized in that: The components of the grinding liquid raw material containing benzotriazole are weighed according to the formula, and the grinding liquid raw material containing benzotriazole is put into a stirrer, and the speed of the stirrer is controlled at 15-60 rpm, and the stirring time is controlled at 20-30 minutes.
4. The process for fine grinding and anti-oxidation treatment of the reflective film surface according to claim 1, characterized in that: The grinding time in S2 is 10-20 minutes, the surface roughness is monitored by a roughness measuring instrument, and the surface roughness Ra is controlled to be 1-2 μm. The grinding time in S3 is 15-30 minutes, and the surface roughness Ra is controlled to be 0.45-0.85 μm. The grinding time in S4 is 30-60 minutes, and the surface roughness Ra is controlled to be 0.1-0.3 μm.
5. The process for fine grinding and anti-oxidation treatment of the reflective film surface according to claim 1, characterized in that: The anti-oxidation coating in S5 comprises the following raw materials in parts by weight: 40-70 parts of film-forming substances, 20-40 parts of solvents, 1-5 parts of titanium dioxide, 1-5 parts of mica powder and 1-10 parts of additives.
6. The process for fine grinding and anti-oxidation treatment of the reflective film surface according to claim 5, characterized in that: The film-forming substance includes the following raw materials in percentage: 30%-50% of silicone resin and 25%-50% of acrylic copolymer; the solvent includes the following raw materials in percentage: 15%-30% of xylene, 15%-40% of butyl acetate, and 20%-30% of deionized water; the auxiliary agent includes the following raw materials in percentage: 30%-80% of isocyanate curing agent, 5%-20% of silicone leveling agent, and 1%-10% of defoaming agent.
7. The process for fine grinding and anti-oxidation treatment of the reflective film surface according to claim 5, characterized in that: The components of the anti-oxidation coating raw materials are weighed according to the formula, and the anti-oxidation coating raw materials are put into a mixer, the speed of the mixer is controlled at 25-75 rpm, and the stirring time is controlled at 10-15 minutes.
8. The process for fine grinding and anti-oxidation treatment of the reflective film surface according to claim 1, characterized in that: The spraying pressure in S5 is 0.3-0.5MPa, the distance between the spray gun and the surface of the reflective film is maintained at 20-30cm, the spraying is divided into three times, and the interval between each time is 5-10 minutes. The final spraying thickness is controlled at 5-10μm, the drying temperature of the dryer is controlled at 80-100℃, and the drying time is controlled at 2-3 hours.
Citation Information
Patent Citations
Manufacturing process of signboard
CN106531010A
Signboard processing method
CN106782054A
Novel signboard preparation method
CN107393439A
Precise grinding fluid for back plate of CVD equipment as well as preparation process and processing method of precise grinding fluid
CN113201285A
Light reflecting material, preparation method and application thereof
CN113667187A